Uso de argilominerais e diatomita como adsorvente de fenóis em águas produzidas na indústria de petróleo - Braga, Renata Martins (2008)
The oil production in Brazil has been increasing each year. Consequently, increasing volumes of water produced are generated with large quantities of contaminants, which brings many problems in disposing of these waters. The concern that the concentrations of contaminants in water produced meet existing laws for disposal of effluents, has been extremely important for the development of different techniques for treatment of water produced. The study of clay minerals as adsorbents of organic contaminants has grown considerably so in order to combine the low cost with the efficiency of environmental preservation and health issues. Thus, this study aims to understand the characteristics of vermiculite clay, sodium bentonite, calcium bentonite and diatomite and evaluate their performance as adsorbents for phenol in the water produced. Through adsorption isotherms it was possible to observe the behavior of these adsorptive clay and diatomite for adsorption of phenol, the main phenolic compound found in water produced. Different concentrations of synthetic solutions of phenol were put in touch with these adsorbents under same conditions of agitation and temperature. The adsorbents were composted adsorptive favorable, but the vermiculite and diatomite showed little capacity for absorption, being suggested for absorbs small concentrations of phenol in the balance isothermal